2019
DOI: 10.1016/j.ejca.2019.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Defining oligometastatic non-small cell lung cancer: A simulated multidisciplinary expert opinion

Abstract: Introduction: Synchronous oligometastatic non-small cell lung cancer (NSCLC) definition varies from 1 metastasis in 1 organ (tumour-node-metastasis 8 [TNM8]), 1e3 metastases (European Society for Medical Oncology [ESMO]), 3 metastases (including mediastinal nodes [MLN]) after systemic treatment to 3e5 metastases in ongoing trials. A single definition is however needed to design/compare trials. To assess oligometastatic NSCLC definitions used by clinical experts in daily practice and its evolution, we redistrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…Whom is regarded as an oligometastatic patient and which treatments are offered tends to differ from physician to physician and has shifted over time, with a tendency to reserve radical local therapy such as SBRT for patients not progressing after systemic therapy (75). Furthermore, as compared to the theoretical definition of oligometastatic disease based on number of lesions, in the real-life setting, physicians tend to be more restrictive as to who they label as oligometastatic (75). Multiple studies have evaluated and suggested clinical prognostic markers to guide patient selection (19,(76)(77)(78)(79), however, these are all based on retrospective data, and have not yet been prospectively validated.…”
Section: Outcome Per Location: An Intricate Interplay Of Dose Volume and Primary Tumormentioning
confidence: 99%
“…Whom is regarded as an oligometastatic patient and which treatments are offered tends to differ from physician to physician and has shifted over time, with a tendency to reserve radical local therapy such as SBRT for patients not progressing after systemic therapy (75). Furthermore, as compared to the theoretical definition of oligometastatic disease based on number of lesions, in the real-life setting, physicians tend to be more restrictive as to who they label as oligometastatic (75). Multiple studies have evaluated and suggested clinical prognostic markers to guide patient selection (19,(76)(77)(78)(79), however, these are all based on retrospective data, and have not yet been prospectively validated.…”
Section: Outcome Per Location: An Intricate Interplay Of Dose Volume and Primary Tumormentioning
confidence: 99%
“…These physicians considered patients to have oligometastatic disease if they had a single metastasis with or without lymph node involvement (N0-1). This practice excludes patients who might otherwise benefit from aggressive local therapy (18).…”
Section: Defining Oligometastasesmentioning
confidence: 99%
“…Recently, the EORTC-LCG published a consensus about the maximal number of metastases allowed to define sOM-NSCLC. Authors evaluated sOM-NSCLC definitions in daily clinical practice in Europe, by a survey and discussion of ten real life cases [7,8]. In the survey, the maximum number of metastases considered as sOM-NSCLC was again variable and 42 % of responders identified 3 as the correct definition [7].…”
Section: Tablementioning
confidence: 99%